Immobilization of selenite from aqueous solution by structural ferrous hydroxide complexes. Issue 22 (27th February 2017) - Zhang, Yong; Fu, Mao; Wu, Deli; Zhang, Yalei
Abstract : Selenium species before and after reaction with FHCs were studied and classified into five groups. Abstract : Ferrous hydroxyl complexes (FHCs) were synthesized by precipitation from Fe(ii ) sulfate salts with sodium hydroxide in an anoxic atmosphere. Effects of the [Fe(ii )]/[OH − ] ratio, dosage and sequential extraction scheme were elaborated on selenium (Se)(iv ) removal by FHCs. Se(iv ) removal by FHCs was more coincident with the pseudo-second order kinetic model. The BET isotherm was the best fit model for the data of equilibrium experiments and R 2 was 0.9902. Se(iv ) removal by FHCs changed with various [Fe(ii )]/[OH − ] ratios, and the maximum removal capacity was 256.41 mg g −1 by FHC ([Fe(ii )]/[OH − ] = 1 : 2). X-ray photoelectron spectroscopy results indicated the mechanism of Se(iv ) removal by FHC([Fe(ii )]/[OH − ] = 1 : 1) to be a combination of adsorption and reduction, whereas reduction was the primary mechanism for Se(iv ) removal by FHC([Fe(ii )]/[OH − ] = 1 : 4). A sequential extraction scheme was employed to study Se speciation before and after the reaction. Se species were classified into five groups (water-soluble, exchangeable, elemental Se, oxide-containing iron state, selenide). Results indicated that elemental Se was the primary species in the reaction products.